1996
DOI: 10.1182/blood.v87.8.3470.bloodjournal8783470
|View full text |Cite
|
Sign up to set email alerts
|

Associations of iron overload in Africa with hepatocellular carcinoma and tuberculosis: Strachan's 1929 thesis revisited

Abstract: We analyzed data from the first study of iron overload in Africans, conducted between 1925 and 1928, to determine whether this common condition is associated with death from hepatocellular carcinoma and/or tuberculosis. In the original study, necropsies were performed on 714 adult blacks from southern Africa. Hepatic and splenic iron levels were measured semiquantitatively in 604 subjects and one of five iron grades was assigned. We examined death from hepatocellular carcinoma or from tuberculosis and the vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(64 citation statements)
references
References 34 publications
4
57
0
1
Order By: Relevance
“…20 A recent proportional mortality analysis of the 1920s autopsy series, in which Strachan first described iron overload in Africans, showed an association between high hepatic iron levels and death from HCC. 21 Because of the limited information obtained in this study concerning the presence of coexisting cirrhosis, we are unable to state whether iron loading is an independent cause of the tumor or acts as an indirect carcinogen by inducing chronic necroinflammatory hepatic disease. The controls did not have liver biopsies performed, and it was not possible to reliably diagnose cirrhosis on the biopsies used to confirm the presence of HCC.…”
Section: Discussionmentioning
confidence: 83%
“…20 A recent proportional mortality analysis of the 1920s autopsy series, in which Strachan first described iron overload in Africans, showed an association between high hepatic iron levels and death from HCC. 21 Because of the limited information obtained in this study concerning the presence of coexisting cirrhosis, we are unable to state whether iron loading is an independent cause of the tumor or acts as an indirect carcinogen by inducing chronic necroinflammatory hepatic disease. The controls did not have liver biopsies performed, and it was not possible to reliably diagnose cirrhosis on the biopsies used to confirm the presence of HCC.…”
Section: Discussionmentioning
confidence: 83%
“…There are two Supporting information Appendix Tables 1 and 2 with a short description of all references which contain additional references .…”
Section: Discussionmentioning
confidence: 99%
“…In the 19th century Trousseau, a Parisian professor in clinical medicine, warned his students that iron supplementation in patients with quiescent tuberculosis (TB) could trigger clinical disease. Several studies confirmed the link between TB and iron, showing that excess in iron markedly increases mycobacterial growth in vitro, in the extra- [9] and intracellular milieu [10], while in vivo it decreases resistance and worsens the outcome in mice [11] and humans [12,13]. The association between iron overload and TB is particularly prominent in Sub-Saharan Africa, illustrated by epidemiological studies [12,13] and reviewed in [14].…”
Section: Introductionmentioning
confidence: 89%